Cellular uptake of PLGA nanoparticles targeted with anti-amyloid and anti-transferrin receptor antibodies for Alzheimer's disease treatment - Loureiro, Joana A.; Gomes, Bárbara; Fricker, Gert; Coelho, Manuel A. N.; Rocha, Sandra; Pereira, Maria Carmo (Colloids and surfaces. B, Biointerfaces, 2016)
During the last few decades, relevant efforts have been reported to design nanocarriers for drug transport through the blood brain barrier (BBB). New drugs, such as peptide iAβ5, capable to inhibit the aggregates associated with Alzheimeŕs disease (AD) are being tested but the most frequent drawback is to reach the brain in the desired concentrations due to the low BBB permeability-surface area. Our approach, as a proof of concept to improve drug transport through the BBB, is based on poly(lactic-co-glycolic acid) (PLGA) nanoparticles with surface functionalized with anti-transferrin receptor monoclonal antibody (OX26) and anti-Aβ (DE2B4) to deliver encapsulated iAβ5 into the brain. Porcine brain capillary endothelial cells (PBCECs) were used as a BBB model to evaluate the system efficacy and toxicity. The uptake of immune nanoparticles with a controlled delivery of the peptide iAβ5 was substantially increased compared to the nanoparticles (NPs) without monoclonal antibody functionalization.
Gesehen am 18.05.2020